DESCRIPTION OF SMOKING BEHAVIOR IN PULMONARY TUBERCULOSIS PATIENTS AT THE PUBLIC HEALTH CENTER LAANTULA JAYA 2014-2015 - Ahmad, Tasrif; Kiay Demak, Indah Puspitasari (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2017)
Background : It is estimated that around one third of the world's population has been infected by Mycobacterium tuberculosis. In developing countries TB cases estimated to be around 95% and 98% of TB deaths worldwide occur in developing countries. Cigarettes and tobacco consumption is one of the major risk factor for the occurrence of various diseases. Data showed the world tobacco epidemic tobacco kills more than 5 million people each year.Methods : descriptive study with retrospective approach to determine the smoking behavior in patients with tuberculosis. The population in this study are patients with pulmonary TB who went to public health centers Laantula Jaya period January 2014 - September 2016 with a sample of 33 people. Sample selection method is purposive sampling.Results : The statistical results processed by SPSS 21.0. Results showed 33 samples obtained from 20 (60.6%) of smokers and 13 people (39.4%) non-smokers. Of overall smokers based on the frequency of smoking 16 people (80%) smoked every day, and 4 (20%) smoked occasionally. Based on the long smoking 3 people (15%) 5-10 years of smoking, 8 (40%) of 10-20 years, and 9 (45%)> 20 years of smoking. Based on the number of cigarettes consumed 2 (10%)> 5 stems, 4 (20%) of 5-10 stems, 14 (70%) of 10-20 stems. Based on the type of cigarettes consumed 16 (80%) cigarette filters and 4 (20%) nonfiter cigarettes. Based on the first cigarette consumption in the morning after waking up 2 people (10%)> 5 minutes, 1 (5%) 6-30 minutes. 14 people (70%) 31-60 minutes and 3 (15%).> 60 minutes. Keywords: Tuberculosis, M. Tuberculosis, Cigarettes, Smoking Latar Belakang: Diperkirakan sekitar sepertiga penduduk dunia telah terinfeksi oleh Mycobacterium Tuberculosis. Di negara-negara berkembang kasus Tuberkulosis diperkirakan sekitar 95% dan 98% kematian akibat TB di dunia terjadi di negara-negara berkembang. Konsumsi rokok dan tembakau merupakan salah satu faktor resiko utama terjadinya berbagai penyakit. Data epidemi tembakau dunia menunjukkan tembakau telah membunuh lebih dari 5 juta orang setiap tahunnya.Metode:  Jenis Penelitian bersifat deskriptif dengan pendekatan retrospektif untuk mengetahui perilaku merokok pada pasien Tuberkulosis. Populasi pada penelitian ini adalah pasien Tuberkulosis Paru yang berobat ke Puskemas Laantula Jaya Periode Januari 2014 – September 2016 dengan jumlah sampel 33 orang. Metode pemilihan sampel adalah purposive sampling.Hasil: Hasil statistik diolah dengan SPSS 21.0. Hasil menunjukkan dari 33 sampel didapatkan 20 orang (60,6%) perokok dan 13 orang (39,4%) bukan perokok. Dari keseluruhan perokok berdasarkan frekuensi merokok 16 orang (80%) merokok setiap hari dan 4 orang (20%) merokok kadang-kadang. Berdasarkan lama merokok 3 orang (15%) 5-10 tahun merokok, 8 orang (40%) 10-20 tahun dan 9 orang (45%) >20 tahun merokok. Berdasarkan jumlah rokok yang dikonsumsi 2 orang (10%) >5 batang, 4 orang (20%) 5-10 batang, 14 orang (70%) 10-20 batang. Berdasarkan jenis rokok yang dikonsumsi 16 orang (80%) rokok filter dan 4 orang (20%) rokok nonfiter. Berdasarkan konsumsi rokok pertama di pagi hari setelah bangun tidur 2 orang (10%) >5 menit, 1 orang (5%) 6-30 menit. 14 orang (70%) 31-60 menit dan 3 orang (15%) .>60 menit. Kata Kunci : Tuberkulosis Paru, M. Tuberkulosis, Rokok, Merokok